Tuning Fermi liquids with polaritonic cavities - Riccardo Riolo; Andrea Tomadin; Giacomo Mazza; Reza Asgari; Allan H. MacDonald; Marco Polini (Proceedings of the National Academy of Sciences, 2025)
The question of whether or not passive subwavelength cavities can alter the properties of quantum materials is currently attracting a great deal of attention. In this article, we show that the Fermi liquid parameters of a two-dimensional metal are modified by cavity polariton modes, and that these changes can be monitored by measuring a paradigmatic magneto-transport phenomenon, Shubnikov–de Haas oscillations in a weak perpendicular magnetic field. This effect is intrinsic, and totally unrelated to disorder. As an illustrative example, we carry out explicit calculations of the quasiparticle velocity of graphene in a planar van der Waals cavity formed by natural hyperbolic crystals and metal gates. The largest effects of the cavity occur when the phonon polariton modes of the former match energetically the graphene plasmon. For typical graphene carrier densities this occurs in the Terahertz spectral range.